Using the Technology: Introducing Point of View Video Glasses Into the Simulated Clinical Learning Environment. Issue 10 (October 2015) - Unknown
Abstract : The introduction of learning technologies into educational settings continues to grow alongside the emergence of innovative technologies into the healthcare arena. The challenge for health professionals such as medical, nursing, and allied health practitioners is to develop an improved understanding of these technologies and how they may influence practice and contribute to healthcare. For nurse educators to remain contemporary, there is a need to not only embrace current technologies in teaching and learning but to also ensure that students are able to adapt to this changing pedagogy. One recent technological innovation is the use of wearable computing technology, consisting of video recording with the capability of playback analysis. The authors of this article discuss the introduction of the use of wearable Point of View video glasses by a cohort of nursing students in a simulated clinical learning laboratory. Of particular interest was the ease of use of the glasses, also termed the usability of this technology, which is central to its success. Students' reflections were analyzed together with suggestions for future use.